Sexual healthcare and at-home STI test collection: attitudes and preferences of transgender women in the Southeastern United States - Van Gerwen, Olivia T.; Austin, Erika L.; Bethune, Carly W.; Sullivan, Patrick S.; Muzny, Christina A. (Frontiers in Public Health, 2023)
Background: HIV and sexually transmitted infections (STIs) disproportionally affect transgender women in the United States, particularly in the Southeast where rates of HIV and bacterial STIs are especially high. Despite the high HIV/STI burden among transgender women, their engagement in sexual healthcare services, including HIV/STI testing, is low. Understanding reasons for this disconnect is essential in developing HIV/STI prevention efforts for this population, especially in the Southeastern US, where access to affirming sexual healthcare providers and resources is limited. We aimed to perform an exploratory qualitative study to describe the attitudes and preferences of transgender women living in Alabama with regards to sexual healthcare and at-home STI test collection. Methods: Transgender women ≥18 years old residing in Alabama were invited to participate in virtual individual in-depth interviews via Zoom. The interview guide explored participant experiences engaging with sexual healthcare services as well as preferences related to extragenital (i.e., rectal, pharyngeal) and at-home STI testing for gonorrhea and chlamydia. A trained qualitative researcher coded transcripts after each interview and iteratively amended the interview guide as themes emerged. Data were coded and thematically analyzed using NVivo qualitative software. Results: Between June 2021-April 2022, twenty-two transgender women were screened and 14 eligible women enrolled. Eight participants were white (57%), and six were black (43%). Five participants (36%) were living with HIV and engaged with HIV care services. Interview themes included preference for sexual healthcare environments specializing in LGBTQ+ care, enthusiasm toward at-home STI testing, an emphasis on affirming patient-provider interactions in sexual healthcare settings, a preference for sexual healthcare providers involved in STI testing who were not cisgender men, and gender dysphoria around sexual health discussions and testing. Conclusion: Transgender women in the Southeastern US prioritize affirming provider-patient interactions, however resources in the region are limited. Participants were enthusiastic about at-home STI testing options, which have the potential to mitigate gender dysphoria. Further investigation into development of remote sexual healthcare services for transgender women should be performed.